Pengaruh Ekonomi Makro Terhadap Indeks Harga Konsumen - Fazhar Sumantri; Umi Latifah (Universitas Bina Sarana Informatika, 2019)
Consumer Price Index (CPI) is an index number indicates the price level of commodity and services must be purchase by consumers inone period. The purpose of the research is to analyze macroeconomics impact to CPI on variable Interest Rate of Credit, Money Supply, USD Exchange Rate, and Inflation as variables. Data used in this research was taken from Central Statistics Agency Indonesia and The Central Bank of The Republic of Indonesia. The result from F test shows significant relationship in Interest Rate of Credit, Money Supply, USD Exchange Rate, and Inflation to CPI. Meanwhile t test shows there is no significant relationship between Money Supply and USD Exchange Rate to CPI, while significant relationship Interest Rate of Credit and Inflation to CPI. Based on Adjuted R Square; Interest Rate of Credit, Money Supply, USD Exchange Rate, and Inflation towards to CPI is 65.6% while the rest of it 34.4% was influenced by other factors.